OPTIMALISASI LAYANAN PEMINJAMAN DAN PENGEMBALIAN DI PERPUSTKAAN MTSN KOTA BATU MELALUI APLIKASI SLIMS - Nurjamilatul Muhairira (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the optimization of borrowing and returning services at the MTsN Kota Batu Library through the implementation of the SLiMS (Senayan Library Management System) application. The background of this study is based on the problem of suboptimal library circulation services due to the use of a manual system, resulting in service delays, recording errors, and limited access to information for users. This study uses a qualitative approach with a case study method, through data collection techniques such as interviews with librarians and library users, direct observation of the service process, and documentation related to the implementation of SLiMS. The results show that the implementation of SLiMS provides significant changes in the effectiveness of library services, especially in the borrowing and returning process. The circulation, cataloging, barcode, and visit report features simplify the recording and tracking of collections, reduce technical errors, and speed up service transactions. Data also shows an increase in the number of visits and borrowing after the use of SLiMS is optimized. Thus, it can be concluded that the implementation of SLiMS plays an important role in improving the quality of library services at MTsN Kota Batu through a more efficient, accurate, and user-friendly automation system. This system not only helps librarians in the management process, but also encourages increased reading interest and literacy activities among students.